2019
DOI: 10.3389/fphys.2019.01005
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Circulating Endothelial Cells and Endothelial Progenitor Cells in the Prediction of Left Ventricular Hypertrophy in Hypertensive Patients

Abstract: Background The main aim of present study is to evaluate the potential role of circulating endothelial cells (CECs) and endothelial progenitor cells (CEPCs) – representing specific markers of endothelial damage, in the prediction of left ventricular hypertrophy (LVH) in hypertensive patients categorized into two groups; mild (MH) and resistant hypertension (RH). Materials and Methods Thirty patients with MH and 28 subjects with RH were involved in the study. In both grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 78 publications
(88 reference statements)
0
6
0
Order By: Relevance
“…In fact, changes in CECs are important predictors of cardiovascular events before the development of atherosclerotic morphological changes ( 52 ). At present, there have been a series of research on the evaluation of CEC functions ( 53 , 54 ). So far, there is no reliable and recognized gold standard for the detection of functional changes of CECs ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, changes in CECs are important predictors of cardiovascular events before the development of atherosclerotic morphological changes ( 52 ). At present, there have been a series of research on the evaluation of CEC functions ( 53 , 54 ). So far, there is no reliable and recognized gold standard for the detection of functional changes of CECs ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with myocardial infarction, alterations of these two subsets may attest to the extent of vascular injury and the associated angiogenic response [ 76 ]. Other results suggested that endothelial injury, observed as an increased CEC number, and impaired regeneration, reflected by a lowered CEPCs/CECs ratio, preceded left ventricular hypertrophy in hypertensive patient’s occurrence [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although meta‐analyses can improve the statistical power and provide more accurate estimates of the effect value, the results depend largely on the criteria for inclusion in the study 63,64 . Molecular biology research has shown that LVH in hypertensive patients is a process evolving from quantitative change to qualitative change 65,66 . This process includes gene translocation of myosin heavy chain, encoding myosin, membrane protein, and energy metabolism of protein gene shift 67‐69 .…”
Section: Discussionmentioning
confidence: 99%
“…63,64 Molecular biology research has shown that LVH in hypertensive patients is a process evolving from quantitative change to qualitative change. 65,66 This process includes gene translocation of myosin heavy chain, encoding myosin, membrane protein, and energy metabolism of protein gene shift. [67][68][69] Brigitte et al have shown that it takes at least 100 days to reverse this process.…”
Section: Bayesian Network Meta-analysesmentioning
confidence: 99%